Identification and characterization of a new branching mutant of Neurospora intermedia from nature - Anita Mukati; Harish Vyas; Alka Vyas (Fungal Genetics Reports, 2015)
Neurospora is a tropical fungus which is found abundantly growing on burnt sugarcane, discarded corn cobs and other burnt vegetation. It is being used as a model organism for understanding growth and branching in fungi. We have isolated and characterized a naturally occurring branching mutant of Neurospora intermedia which may be useful for understanding growth and branching in fungi.